Characterizing the structural formation of epoxy-amine networks: The effect of monomer geometry. (8th November 2016) - Riad, Keroles B.; Schmidt, Rolf; Arnold, Alexandre A.; Wuthrich, Rolf; Wood-Adams, Paula M.
Abstract: We develop an approach for quantifying cure that applies thermodynamic modelling to interpret DSC data that is consistent with solid state NMR. The effect of elements of monomer geometry, such as the angle between functional groups and the distance between them, on curing of epoxy-amine thermosets is explored experimentally using this new technique. The effect of the angle between functional groups on the glass transition temperature of the final cured network is significant. The effect of spacing between functional groups is masked by the rigidity of the spacer. Our approach to interpreting DSC data allows us to detect processes that would have been missed otherwise. This is exemplified by the observation of slow exothermic deterioration reaction. Our NMR results indicate that significant etherification occurs at 140 °C, unlike the commonly held belief that it is insignificant at such low temperatures. Graphical abstract: Highlights: Effect of basic monomer geometry on Tg and degradation is explored. DSC technique accurately measures cure and detects other exothermic processes. Unexpected large amount of etherification observed at low curing temperatures.